2022
DOI: 10.3389/fimmu.2022.985280
|View full text |Cite
|
Sign up to set email alerts
|

Decreased TCF1 and BCL11B expression predicts poor prognosis for patients with chronic lymphocytic leukemia

Abstract: T cell immune dysfunction is a prominent characteristic of chronic lymphocytic leukemia (CLL) and the main cause of failure for immunotherapy and multi-drug resistance. There remains a lack of specific biomarkers for evaluating T cell immune status with outcome for CLL patients. T cell factor 1 (TCF1, encoded by the TCF7 gene) can be used as a critical determinant of successful anti-tumor immunotherapy and a prognostic indicator in some solid tumors; however, the effects of TCF1 in CLL remain unclear. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…or MDS, the reason is thought that lower BCL11B related lower T cell activity. 18,36 In contrast, BCL11B is also considered as oncogene in T-ALL, 22,37 overexpression of BCL11B is frequently identified in T-ALL, inhibition of BCL11B effectively induces growth retardation and apoptosis of T-ALL cells. [22][23][24]38,39 These findings were consistent with present study that TCL patients harboring BCL11B mutation might predict favorable prognosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…or MDS, the reason is thought that lower BCL11B related lower T cell activity. 18,36 In contrast, BCL11B is also considered as oncogene in T-ALL, 22,37 overexpression of BCL11B is frequently identified in T-ALL, inhibition of BCL11B effectively induces growth retardation and apoptosis of T-ALL cells. [22][23][24]38,39 These findings were consistent with present study that TCL patients harboring BCL11B mutation might predict favorable prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, BCL11B haplo‐insufficiency occurs in each major T‐ALL molecular subtypes, such as early T‐cell precursor and TAL1‐positive subtypes, which exhibit differentiation arrest at different thymocyte development stages 35 . Moreover, decreased BCL11B expression was associated adverse clinical outcomes for patients with chronic lymphocytic leukemia (CLL) or MDS, the reason is thought that lower BCL11B related lower T cell activity 18,36 . In contrast, BCL11B is also considered as oncogene in T‐ALL, 22,37 overexpression of BCL11B is frequently identified in T‐ALL, inhibition of BCL11B effectively induces growth retardation and apoptosis of T‐ALL cells 22–24,38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…The Ethics Committee of Hunan University of Chinese Medicine exempted the use of public database data from ethical review. We obtained AD-related targets from DisGeNET and screened for overlaps between the predicted targets of the compounds and AD-related targets using the VENNY online tool [ 21 ]. The common targets were considered potential targets of QFY for treating AD and were imported into Cytoscape to construct the C-T-AD network.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, recent studies have shown that TCF1 is essential for maintaining CD8+ T CM cells and serves as a positive biomarker for prolonged survival and effective responses to PD1 inhibitors in various solid tumors and hematological malignancies (82)(83)(84)(85). Undoubtedly, high-level IRF4 is beneficial to the initial effector function, but sustained overexpression of IRF4 inhibits the expression of TCF1, which further damages the production of antigen-specific T CM cells and is not conductive to the rapid effect function in recall responses (24).…”
Section: Irf4 Maintains the Effector Function Of Cd8+ Memory T Cellsmentioning
confidence: 99%